Tourism in Supporting Indonesia's Creative Industry: Ansoff Matrix Approach - Arif, Nina Fapari; Rahman, Fathi Habibatur; Setyani, Atik (RSF Conference Series: Business, Management and Social Sciences, 2025)
The creative industry plays a strategic role in driving economic growth, creating jobs, strengthening cultural identity, and enhancing Indonesia's global competitiveness. However, its development still faces challenges, including limited infrastructure, low digital literacy, uneven human resource skills, and limited access to financing. This study aims to analyze the growth strategies of the creative industry and tourism in Indonesia using the Ansoff Matrix framework, employing both quantitative and qualitative approaches. Data were obtained from a BPS survey and in-depth interviews with 48 creative SMEs, then analyzed using NVivo. The results show that growth strategies can be realized through collaboration (co-creation) between creative industry SMEs and tourism destination managers, as well as the use of digital technology and social media. Collaboration between the creative industry and tourism can increase tourist appeal while empowering the local economy. This study highlights the importance of synergy among the government, the private sector, communities, and academics in fostering sustainable creative tourism, enhancing international service standards, and expanding access to financing for product innovation. These findings provide an empirical contribution and offer a strategic framework for the development of the creative economy and tourism, particularly in developing countries.